2021
DOI: 10.3390/ma14226945
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular, Histological, Clinical, and Radiological Analyses of Dental Implant Bone Sites Prepared Using Magnetic Mallet Technology: A Pilot Study in Animals

Abstract: Background. A new instrumentation exploiting magneto-dynamic technology (mallet) proposed for implant site preparation was investigated. Methods. In the tibias of three minipigs, two sites were prepared by mallet and two by drill technique. Primary stability (ISQ) was detected after implant positioning (T0) and at 14 days (T14). X-rays and computed tomography were performed. At T14, bone samples were utilized for histological and biomolecular analyses. Results. In mallet sites, histological evaluations evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The use of the handpiece is also very simple; in fact, it can be handled with one hand. For whatever procedure is used (from extraction to split crest), [9][10][11][12][13] the forces are applied with great precision and in a predictable manner, ensuring total control by the operator during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the handpiece is also very simple; in fact, it can be handled with one hand. For whatever procedure is used (from extraction to split crest), [9][10][11][12][13] the forces are applied with great precision and in a predictable manner, ensuring total control by the operator during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The MM, compared to the TD technique, demonstrates a greater tendency to maintain the structure of the trabecular bone and causes less damage to the cortex and spongy bone. Additionally, it enhances the density of the remaining bone [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Bennardo et al 49 conducted a systematic review to evaluate the effectiveness of the magnetic mallet in oral and implant surgery, suggesting the need for more extensive randomised controlled trials. Schierano et al, 50 in their pilot study in animals using magnetic mallet technology for dental implant sites, showed effectiveness in implant site preparation, particularly in poor bone quality cases. Bruschi et al, 51 in a retrospective study, analysed flapless trans-crestal maxillary sinus floor elevation with simultaneous dental implant placement, finding it safe and effective with low morbidity.…”
Section: Discussionmentioning
confidence: 99%